2D electrical resistivity imaging of tantalite-bearing veins in Kaiama, Nigeria. Issue 1 (31st December 2022) - Raji, Wasiu Olanrewaju; Bale, Rafiu Babatunde
ABSTRACT: The utility of the electrical resistivity (ER) method of geophysics for delineating tantalite-rich zones is demonstrated. To avoid negative environmental consequences, the local authority refused the use of trial-and-error method by the artisanal and small-scale miners. 2D ER method was applied to delineate the locations and dimensions of the tantalite-rich zones. Data were acquired along nine profiles in the study area at predetermined locations, after reconnaissance field mapping, using SuperSting R8/IP Earth Resistivity Metre, 84 electrodes, and the full accessories. Each profile was 249 m long with 84 electrodes coupled to the ground at 3 m intervals on a straight line following the dipole–dipole electrode array. Data acquired were processed to obtain tomographic images of the subsurface. The results revealed low resistivity anomalies (1–60 Ωm) corresponding to tantalite-rich quartz veins that intruded into the high-resistive migmatite-gneisses-schist complex. The tantalite-rich zones were located at depths ranging from near-surface to about 45 m, their lengths and thicknesses range from 40 to 220 m and 3 to 32 m, respectively. A pit dug along profile six confirmed the low resistivity structures to be tantalite-rich quartz veins. Findings from the study are useful for economic evaluation of similar deposits, determining the extent of excavation required for mining, and planning land reclamation.